Features functional coordination and force readiness of young men in grades 9—11 - Іващенко, О. В. (Physical Education Theory and Methodology, 2014)
Purpose — to determine patterns of motion and functional training high school students. Material and methods. To achieve the objectives adopted the following methods: analysis of scientific literature, teacher testing and treatment methods of mathematical statistics research results. In the study involved 36 boys in grade 9, 11 — 10 class 12 — 11 form. Conclusions. In the test results of students grades 9 and 10 there are statistically significant differences in the functional fitness of respiratory and cardiovascular systems, as well as coordination and strength training. For functional preparedness young assessed as healthy untrained. The test results are observed statistically significant differences between boys 9 and 11 for the performance tests 1, 2, 3 and 9 (p <0,05; 0,001). For the functional state of respiration and circulation boys in grade 11 are rated as healthy trained. Statistically significant differences between boys 10 and 11 are observed in the tests that characterize functional, coordination and preparedness own power (p <0,001). Boys 11 classes have better preparedness on the results of a battery of tests (p <0,001). Boys 11 classes perform better speed, static strength, coordination and functional state of the respiratory and cardiovascular systems. Standardized canonical discriminant function coefficients can determine the value contribution of variables in the function result. With the largest contribution to the canonical function variables included 1 9, 3 and 6: the higher the value of these variables, the more important functions. With the largest contribution to the canonical function of 2 variables are 8, 9 and 2: The higher the value of these variables, the more important functions. The first function to 79.3% explained variance of results, the second — 20,7%. The foregoing suggests the possibility age classification vidminostey boys grades 9—11 based on functional testing, power and coordination training. Structural factors canonical discriminant function shows that feature most significantly associated with the number 9, 7 and 6 variables: thus a significant difference between boys grades 9—11 have developed functional status and motor abilities: test Serkina, speed strength, coordination and own power.